Cellular mechanisms of the 5-HT7 receptor-mediated signaling - Guseva, Daria; Wirth, Alexander; Ponimaskin, Evgeni (Frontiers in Behavioral Neuroscience, 2014)
Serotonin (5-hydroxytryptamine or 5-HT) is an important neurotransmitter regulating a wide range of physiological and pathological functions via activation of heterogeneously expressed 5-HT receptors. The 5-HT7 receptor is one of the most recently described members of the 5-HT receptor family. Functionally, 5-HT7 receptor is associated with a number of physiological and pathological responses, including serotonin-induced phase shifting of the circadian rhythm, control of memory as well as locomotor and exploratory activity. A large body of evidence indicates involvement of the 5-HT7 receptor in anxiety and depression, and recent studies suggest that 5-HT7 receptor can be highly relevant for the treatment of major depressive disorders. The 5-HT7 receptor is coupled to the stimulatory Gs-protein, and receptor stimulation results in activation of adenylyl cyclase (AC) leading to a rise of cAMP concentration. In addition, this receptor is coupled to the G12-protein to activate small GTPases of the Rho family. This review focuses on molecular mechanisms responsible for the 5-HT7 receptor-mediated signaling. We provide detailed overview of signaling cascades controlled and regulated by the 5-HT7 receptor and discuss the functional impact of 5-HT7 receptor for the regulation of different cellular and subcellular processes.